Experimental analysis of the impact of particles on the cavitating flow - Gregorc, Boštjan (Strojniški vestnik, 2012)
The purpose of this paper is to present an analysis of the impact of solid particles on the development of cavitating flow conditions around a hydrofoil. Experimental studies have been conducted in a cavitation tunnel with three different mixtures of particles and water. We used a particle-like properties, such as are found in river water, and with increasing mass concentration. We performed measurements of torque and the relative noise in the hydrofoil. The point in the formation of vapour phase on the hydrofoil and the pronounced frequency effect were determined by measuring the relative noise. Based on the analysis the results show that the particles increase the intensity and extent of cavitation.
Keywords: delci; hidravlične črpalke; hrup; kavitacija; meritve; turbine; voda